2016
DOI: 10.1175/bams-d-14-00193.1
|View full text |Cite
|
Sign up to set email alerts
|

Where Are the Lightning Hotspots on Earth?

Abstract: Previous total lightning climatology studies using Tropical Rainfall Measuring Mission (TRMM) Lightning Imaging Sensor (LIS) observations were reported at coarse resolution (0.5°) and employed significant spatial and temporal smoothing to account for sampling limitations of TRMM’s tropical to subtropical low-Earth-orbit coverage. The analysis reported here uses a 16-yr reprocessed dataset to create a very high-resolution (0.1°) climatology with no further spatial averaging. This analysis reveals that Earth’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
258
2
23

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(303 citation statements)
references
References 58 publications
20
258
2
23
Order By: Relevance
“…La más reciente publicación de resultados de medición satelital de la NASA (Albrecht, 2016) muestra, por ejemplo, que el sitio de mayor actividad de rayos del mundo estaría ubicado en la región del Catatumbo y específicamente en el lago de Maracaibo y de las 10 poblaciones de mayor actividad de rayos en la zona de Suramérica, 7 están ubicadas en Colombia. La actividad de rayos en esta región llevó a Alexander von Humboldt (Humboldt, 1956) a llamar este fenómeno como el "rayo del Catatumbo".…”
Section: La Historia Y La Literatura En La Interpretación Del Rayounclassified
“…La más reciente publicación de resultados de medición satelital de la NASA (Albrecht, 2016) muestra, por ejemplo, que el sitio de mayor actividad de rayos del mundo estaría ubicado en la región del Catatumbo y específicamente en el lago de Maracaibo y de las 10 poblaciones de mayor actividad de rayos en la zona de Suramérica, 7 están ubicadas en Colombia. La actividad de rayos en esta región llevó a Alexander von Humboldt (Humboldt, 1956) a llamar este fenómeno como el "rayo del Catatumbo".…”
Section: La Historia Y La Literatura En La Interpretación Del Rayounclassified
“…According to several studies about the lightning climatology around the Earth, the Congo Basin is considered as the most active region with either a large maximum or two distinct ones (Christian et al, 2003;Williams and Sátori, 2004;Albrecht et al, 2011Albrecht et al, , 2016Cecil et al, 2014;Soula et al, 2016). Actually, the features of the maximum area depend on the spatial resolution considered in the calculation of the flash rate density (FRD) and the scale resolution in the graphic representation.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the features of the maximum area depend on the spatial resolution considered in the calculation of the flash rate density (FRD) and the scale resolution in the graphic representation. Albrecht et al (2016) performed a very detailed analysis of FRD thanks to Lightning Imaging Sensor (LIS) data around the Earth by using several spatial resolutions. They showed the features of the maxima FRD strongly depend on the spatial resolution and on the duration of the period considered for the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several studies using different methodologies [3] [4] [5] [6], have already shown that the Southeast Region of Brazil is inserted in the spatial context of the regions of the world with the highest incidence of this phenomenon. Only in the State of São Paulo, there are around 700,000 lightning per year [1].…”
Section: Introductionmentioning
confidence: 99%